2018
DOI: 10.1155/2018/7231818
|View full text |Cite
|
Sign up to set email alerts
|

Tracking of Physical Fitness of Primary School Children in Trier: A 4-Year Longitudinal Study

Abstract: Objective The aim of this study is to measure the motor development and tracking of physical fitness (PF) components of primary school children of Trier in Germany. Methods Two longitudinal cohorts, of 1768 children (915 f, 853 m) aged 5–11, were measured. In longitudinal cohort 1, a total of 116 female and 137 male participants aged 6.80 ± 0.42 years at baseline were measured four times from grade 1 to grade 4 (response: 40.4%). Participants of longitudinal cohort 2 (166 f, 149 m; 6.70 ± 0.36 years at baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
3
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 29 publications
(53 reference statements)
4
21
3
5
Order By: Relevance
“…In terms of physical fitness, boys obtained better results than girls in all physical fitness components except flexibility. These results confirm previous research and show that girls have an advantage in flexibility [7,46], while boys perform better in conditioning components [7,46]. Although the participants were not in puberty period, differences in physical fitness between genders were significant.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In terms of physical fitness, boys obtained better results than girls in all physical fitness components except flexibility. These results confirm previous research and show that girls have an advantage in flexibility [7,46], while boys perform better in conditioning components [7,46]. Although the participants were not in puberty period, differences in physical fitness between genders were significant.…”
Section: Discussionsupporting
confidence: 90%
“…Physical fitness is an important factor for social development of children and is associated with a variety of health benefits [7]. There is consensus that being physically fit reduces the risk of cardiovascular diseases [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning motor abilities, a recently published study showed differences between boys and girls aged 5–11 years (Roth et al, 2018): Girls were better than boys in balancing backward, stand-and-reach, and jumping sideways, whereas boys were faster than girls in running events. Several meta-analytical studies have examined possible gender differences in academically important factors such as mathematical ability, verbal skills, and spatial ability.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the gender gap in motor ability in children, a recently published study indicated a difference between 5- to 11-year-old boys and girls: girls performed better in a balancing backwards task and a task to stand and reach and jumping sideways, whereas boys obtained better results in a 20-meter sprint and a 6-minute run [5]. Gender differences in motor ability could be detected in the preschool years: 3- to 4-year-olds differed in the Total Motor Score, fine motor skill and a balance task, while there were no sex differences for the Total Motor Score or balance in 5- to 6-year-olds.…”
Section: Introductionmentioning
confidence: 99%